TABOO LANGUAGEIN MAENGGI KI’S MY ID IS GANGNAM BEAUTY - Ariyanti Silaen; Wenilia Halawa; Desmalia Purba (LPPM Universitas Darma Agung, 2023)
In this study, the researcher analyzes taboo language phenomenon in a comic entitled My ID Is Gangnam Beauty especially on the kinds of taboo language used uttered by the characters with good academic background. The objectives of this research are to identify and describe the types of taboo language uttered by the characters of Maenggi Ki’s My ID Is Gangnam Beauty, to find out the most dominant types of taboo language of taboo language uttered by the characters in Maenggi Ki’s My ID Is Gangnam Beauty and to find out the reasons for the most dominant type of taboo language uttered by the characters in Maenggi Ki’s My Id Is Gangnam Beauty. The researcher uses a descriptive qualitative method based on Batistella (2005) theory and Wardhaugh (2006) theory. The technique of analyzing data are: classifying, analyzing, discussing and reporting. Based on the result on the analysis, there are four types of taboo language that found in My Id Is Gangnam Beauty: Ephitet, Obscenity, Profanity, and Vulgarity. The most dominant type is Ephitets type which are found one hundred six (106) times out of 84 episodes. There are 4 the functions that can be reasons of most dominant taboo language is occur that found in My ID Is Gangnam Beauty: To Draw Attention to Oneself, To Show Contempt, To be Provoke, To Mock Authority out of 84 episodes.